ANALISIS KORESPONDENSI PADA POLA HUBUNGAN ANTARA JENIS BENCANA DAN STATUS KORBAN DI SUMATERA TAHUN 2024 - Muhammad Al-Farisy; Riska Mulyani; M. Riswan; Tarisa Humaira; Lathifah Putri Adani (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2026)
CORRESPONDENCE ANALYSIS OF THE RELATIONSHIP PATTERN BETWEEN DISASTER TYPES AND VICTIM STATUS IN SUMATERA IN 2024 This study analyzes the relationship between provinces, types of disasters, and types of disaster victims in 10 provinces on Sumatra Island using correspondence analysis. The data includes seven disaster types and five victim categories from Aceh, North Sumatra, West Sumatra, Riau, Riau Islands, Jambi, Bengkulu, South Sumatra, Bangka Belitung Islands, and Lampung. Descriptive results show floods as the most frequent disaster, while the